Efficacy and safety of different noninvasive ventilation strategies for postextubation respiratory support in Neonatal Respiratory Distress Syndrome: a systematic review and network meta-analysis - Yang, Jiayi; Mei, Hua; Wang, Xiaoli; Zhang, Jie; Huo, Mengyue; Xin, Chun (Frontiers in Pediatrics, 2024)
The study aimed to compare the efficacy and safety of different noninvasive ventilation (NIV) modalities as primary respiratory support following extubation in Neonatal Respiratory Distress Syndrome (NRDS).: A search was conducted in PubMed, Embase, Cochrane, Web of Science, China National Knowledge Network (CNKI), Wanfang database, VIP, and Chinese Biomedical Literature databases with a search time limit of April 2024 for the year of construction, and included randomized controlled clinical trials of different modes of noninvasive respiratory support after extubation in NRDS. The primary outcome indicators were the need for re-tracheal intubation within 72 hours of extubation on noninvasive ventilatory support and carbon dioxide retention (PCO2) 24 hours after extubation. Secondary outcome indicators included the incidence of bronchopulmonary dysplasia (BPD), nasal injury, pneumothorax, intraventricular hemorrhage (IVH) or periventricular white matter softening (PVL), retinopathy of prematurity (ROP), necrotizing enterocolitis (NEC), and mortality rate. A systematic review and network meta-analysis of the literature was performed by two investigators who screened, extracted, and evaluated the quality of the data. A systematic review and network meta-analysis were then performed using R software. Results: A total of 23 studies involving 2331 neonates were analyzed. These studies examined four noninvasive respiratory modalities: continuous positive airway pressure ventilation (NCPAP), noninvasive intermittent positive pressure ventilation (NIPPV), bi-level positive airway pressure ventilation (N-BiPAP), and noninvasive high-frequency oscillatory ventilation (NHFOV). Results indicated that NHFOV, NIPPV, and N-BiPAP were significantly more effective than NCPAP in reducing the risk of reintubation (all P < 0.05), with NHFOV being the most effective. For carbon dioxide clearance, NHFOV outperformed both NIPPV and NCPAP (P < 0.05). Regarding the reduction of bronchopulmonary dysplasia (BPD) incidence, NHFOV and NIPPV showed a significant advantage over NCPAP.Conclusions: This network meta-analysis (NMA) suggested that NHFOV is the most effective mode of noninvasive respiratory support post-extubation, while NCPAP is the least effective.However, these findings should be interpreted with caution due to the limited number and quality of the studies included.